2020
DOI: 10.1371/journal.pone.0234336
|View full text |Cite
|
Sign up to set email alerts
|

Gamble for the needy! Does identifiability enhances donation?

Abstract: To investigate how neediness and identifiability of a recipient influence the willingness of a donor to invest resources in charity-like lotteries we propose a new game, called 'need game'. Similar to the dictator game, the need game includes two players, one active player (the donor or dictator) and one passive player (the recipient). Both players require a minimum need (N D and N R), expressed in terms of points. The donor is endowed with K D points and must retain at least N D points, i.e., the need, with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
(61 reference statements)
1
7
1
Order By: Relevance
“…The frequency of risky choices increased with increasing probabilities of winning the gamble. This finding supports previous research investigating the role of probabilities in risky choice framing paradigms [ 8 , 12 , 17 , 19 ]. However, despite the similar designs, it contradicts the results of De Martino et al [ 11 ] and Sundelin et al [ 55 ] who found less risky choices for higher than for lower probabilities.…”
Section: Summary and Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The frequency of risky choices increased with increasing probabilities of winning the gamble. This finding supports previous research investigating the role of probabilities in risky choice framing paradigms [ 8 , 12 , 17 , 19 ]. However, despite the similar designs, it contradicts the results of De Martino et al [ 11 ] and Sundelin et al [ 55 ] who found less risky choices for higher than for lower probabilities.…”
Section: Summary and Discussionsupporting
confidence: 91%
“…When using longer time limits (e. g., 8s vs. 32s) risk-taking seem to decrease under shorter time limits [ 57 , 58 ]. Other studies did not find any main effects of time limits on risky choice behavior at all [ 8 , 12 , 19 ]. Furthermore, a time limit effect may also depend on individual differences [ 17 ].…”
Section: Summary and Discussionmentioning
confidence: 86%
See 3 more Smart Citations